Analyzing the Implementation of the LAMDIK Accreditation System at a Leading State Islamic University in Indonesia - Nuryana, Amiatun; Yuwana, Setya; Novaria, Rachmawati; Fahmi, Lukman; Handoko, V. Rudy (International Journal of Emerging Research and Review, 2025)
Objective: This study aims to analyze the implementation of the LAMDIK accreditation system at a leading State Islamic University in Indonesia, focusing on institutional readiness, implementation challenges, and the extent to which accreditation reforms have fostered a sustainable quality culture. Method: A qualitative case study approach was employed within the Early Childhood Islamic Education (ECIE) program at UIN Sunan Ampel Surabaya. Data were collected through semi structured interviews, non-participant observation, and document analysis. The data were analyzed using Miles and Huberman’s (2014) interactive model data condensation, display, and conclusion drawing supported by triangulation and member checking to ensure validity. Results: The findings reveal a moderate level of implementation success. The university achieved structural compliance with LAMDIK standards meeting lecturer qualifications, curriculum alignment, and operational SPMI systems but struggled with deep cultural internalization of quality principles. Limited doctoral qualified lecturers, fragmented data management, and inconsistent communication across units were identified as major barriers. Nevertheless, institutional initiatives in digital accreditation systems, curriculum revision, and quality assurance mark tangible progress. Novelty: This study extends Edwards III’s policy implementation framework to the context of Islamic higher education accreditation, showing that accreditation success depends not only on compliance but also on organizational learning and cultural transformation. The findings highlight how UIN Sunan Ampel Surabaya is transitioning from procedural compliance toward a developing quality driven academic culture.